Intersectionality and marginalization in Viet Thanh Nguyen’s The Sympathizer: A study of minority literature - Alrefai, Abeer A.; Elhalafawy, Ayman; Adel, Mohammed Abou; El-Mezyen, Badea; Lahiani, Hanene; Khalifa, Samir H. (Research Journal in Advanced Humanities, 2026)
This paper examines intersectional marginalization in Viet Thanh Nguyen’s The Sympathizer by analyzing how gender, race, and colonial legacy intersect to produce forms of exclusion within the novel’s narrative framework. While existing scholarship has largely focused on racial hybridity, diasporic identity, and postcolonial memory—primarily through readings centered on the male narrator—this study addresses a critical gap by foregrounding the gendered dimensions of marginalization that remain comparatively underexamined. Accordingly, the analysis concentrates on selected female characters, including the narrator’s mother, Lan, Madame, and other minor female figures, whose narrative positioning exposes recurring patterns of silencing, objectification, and peripheralization. The findings demonstrate that the novel constructs gendered exclusion through the convergence of patriarchal norms, racial hierarchies, class relations, and the enduring effects of colonial violence and war. Although The Sympathizer offers a sustained critique of imperial domination and racialized representation, it simultaneously reproduces subtle forms of gendered marginalization by confining female characters to symbolic, sexualized, or narratively marginal roles. In this context, the male narrator functions as a narrative mediator through which these gendered power relations are articulated and, at times, reinforced, thereby underscoring the necessity of an intersectional approach for reassessing the novel’s critical and political scope.